E-Marketing Methods and Application For Successful Marketing in Global Marketing Scenario - Senthil Nathan, C. (Indian Journal of Marketing, 2009)
There has been rapid penetration of Internet in India in recent years and Internet users are growing many fold. According to Internet and Mobile Association of India, there were close to 60 million internet users in the country. As media clutter and segmentation become more, the rule than the exception along with growing youth brigade of Indian consumers ’E-marketing’ is gaining prominence among marketers and ad agencies.